Association between platelet indices and first trimester miscarriage. Issue 5 (July 2016) - Akin, Melike N.; Kasap, Burcu; Yuvaci, Hilal U.; Turhan, Nilgun
Abstract : We aimed to measure the effect of several potential risk factors on first trimester miscarriage. A total of 169 cases were included in the present study. Patients were selected from women who had first trimester miscarriage (n = 78) and controls were selected from the women who had given birth at term (> 37 weeks of gestation) to healthy infants (n = 91). Compared with the control group, in the miscarriage group gestational age (8.9 ± 2.8 weeks and 8.1 ± 2.2 weeks, respectively, P = 0.032), mean platelet volume (MPV) (8.8 ± 1 and 9.5 ± 1.1 fl, respectively, P < 0.001), plateletcrit (0.209 ± 0.03% and 0.241 ± 0.05%, respectively, P < 0.001), and platelet/lymphocyte ratio (128 ± 37 and 145 ± 60, respectively, P = 0.027) were significantly higher. Multivariate analysis showed that first trimester miscarriage development ratio was 1.909 times higher when MPV value was over 9.1 fl (P < 0.001); 9.147 times higher when plateletcrit value was over 0.219% (P = 0.022). Receiver operating characteristic analysis was performed to determine diagnostic MPV and plateletcrit values for first trimester miscarriage. MPV value greater than 9.1 fl determined miscarriage with 60% sensitivity and 65% specificity, while plateletcrit value greater than 0.219% determined miscarriage with 64.5% sensitivity and 64.7% specificity. MPV and plateletcrit values were strongly associated with first trimester miscarriage. Platelet indices can be used for prediction of fetal loss.